Genetic assessment of five breeding populations of abalone (Haliotis midae) through a comparative Performance Testing Scheme - Vlok, Arnoldus Christiaan (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.